Non-conjugated diketone as a linkage for enhancing the rate performance of poly(perylenediimides). Issue 37 (1st September 2020) - Gao, Xiang; Chen, Yuan; Gu, Chengjun; Wen, Jing; Peng, Xiang; Liu, Jiacheng; Zhang, Zhanhui; Zhang, Qi; Liu, Zhitian; Wang, Chengliang
Abstract : Non-conjugated carbonyl groups as the linkage facilitated the rate performance of polyimides in sodium-ion batteries. Abstract : The electrochemically active carbonyl groups in cyclized diketones or conjugated carboxylates have been widely studied as electrode materials. But the effects of non-conjugated carbonyl groups on the electrochemical properties have been overlooked. This contribution studies the effects of non-conjugated carbonyl groups on perylenediimide (PDI)-based polyimides (poly(PDI)s) as a proof-of-concept. The results show that non-conjugated diketone as a linkage can enhance the rate performance and cyclability of poly(perylene diimide)s: a capacity of 120.9 mA h g −1 at 2 A g −1 after 1000 cycles with a decay rate of 0.0039 mA h g −1 per cycle can be obtained, which is among the best performance of polyimide-based electrodes. The experiments and simulations prove that the diketone groups in the linkage facilitate the adsorption and diffusion of Na +, which contribute to the outstanding rate performance. Therefore, our work highlights the importance of non-conjugated diketone groups as the linkage for enhancing the rate performance of sodium-ion batteries.